Pengembangan media powerpoint interaktif materi mitigasi dan adaptasi bencana alam untuk meningkatkan hasil belajar siswa - Sholichah, Zumrotus; Suharto, Yusuf; Sahrina, Alfi; Soelistijo, Djoko (Universitas Negeri Malang, 2023)
The function of schools in the 21st century has expanded, teachers are required to create learning following the standards of the educational process to produce quality graduates and be able to overcome complex problems. One of the efforts in improving students' abilities is through the learning process. Nowadays, students need learning that involves visual representation of data to attract attention. It can be represented in interactive Powerpoint media. The aim of this study is to produce a viable product in the form of interactive Powerpoint media material on natural disaster mitigation and adaptation to improve student learning outcomes. Research procedure used is ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The data used is quantitative with the collection technique through assessment questionnaires, response questionnaires, and tests. Once collected, the data are analyzed by percentage descriptive analysis techniques. Product trials were carried out in two classes, namely the experimental class (XI 6) and the control class (XI 5). The results of validating the feasibility of media experts obtained 93.3 percent and design experts 70.1 percent. The results of the product trial to students received 83.2% responses and from teachers 83.5 percent. As well as the average value obtained by XI 6 is higher than XI 5. Thus, it is known that the use of interactive Powerpoint media for natural disaster mitigation and adaptation materials has a positive influence on student learning outcomes. Fungsi sekolah di abad-21 mengalami perluasan, guru diharuskan menciptakan pembelajaran sesuai dengan standar proses pendidikan untuk menghasilkan lulusan berkualitas dan mampu mengatasi permasalahan yang kompleks. Salah satu upaya dalam meningkatkan kemampuan siswa yaitu melalui proses belajar. Saat ini, siswa membutuhkan pembelajaran yang melibatkan representasi visual data untuk menarik perhatian. Hal tersebut dapat direpresentasikan dalam media Powerpoint interaktif. Tujuan penelitian ini adalah menghasilkan produk yang layak berupa media Powerpoint interaktif materi mitigasi dan adaptasi bencana alam untuk meningkatkan hasil belajar siswa. Prosedur penelitian menggunakan model ADDIE (Analyze, Design, Development, Implementation, dan Evaluation). Data yang digunakan berjenis kuantitatif dengan teknik pengumpulannya melalui angket penilaian, angket tanggapan, dan tes. Setelah terkumpul, data dianalisis dengan teknik analisis deskriptif persentase. Uji coba produk dilakukan kepada dua kelas, yaitu kelas eksperimen (XI 6) dan kelas kontrol (XI 5). Hasil validasi kelayakan ahli media memperoleh 93,3 persen dan ahli desain 70,1 persen. Hasil uji coba produk kepada siswa memperoleh tanggapan 83,2 persen dan dari guru 83,5 persen. Serta nilai rata-rata yang diperoleh XI 6 lebih tinggi dibanding XI 5. Demikian, diketahui penggunaan media Powerpoint interaktif materi mitigasi dan adaptasi bencana alam memberi pengaruh positif terhadap hasil belajar siswa.